Increasing Website Traffic with the On-Page Search Engine Optimization Approach: A Case Study of LaskarKoinSeribu.org - Jihadi, Hilman; Dade Maulana; Aryanti Kristantini (Digitus : Journal of Computer Science Applications, 2025)
This study aims to increase traffic to the LaskarKoinSeribu.org website, an Islamic-based donation platform, through the implementation of On-Page SEO strategies. A comprehensive analysis identified several key issues, including low organic traffic, suboptimal keyword usage, less SEO-friendly URL structures, inadequate content optimization, and weak internal linking. To address these challenges, this study utilizes various SEO tools such as Google Keyword Planner, Semrush, and Meta Tags Analyzer to design strategies based on targeted keywords, including "Islamic donation," "charity," and "Bogor donation." The implementation of On-Page SEO techniques leads to a significant increase in website traffic, with rankings improving to the top position on Google search results compared to prior SEO efforts. Key factors contributing to this success include technical optimization, content improvement, and long-tail keyword integration, all of which enhance website visibility, user engagement, and donation conversions. The results highlight the effectiveness of On-Page SEO in strengthening the platform’s online presence and supporting its social and religious mission by making donation opportunities more accessible to the target audience. This study demonstrates that proper SEO strategies can serve as a powerful tool for non-profit platforms in increasing digital reach and maximizing social impact.